Theoretical Investigation of CsBX3 (B = Pb, Sn; X = I, Br, Cl) Using Tran–Blaha Modified Becke–Johnson Approximation for Flexible Photoresponsive Memristors. Issue 7 (29th May 2021) - Khera, Ejaz Ahmad; Ullah, Hafeez; Imran, Muhammad; Khalil, R. M. Arif; Hussain, Fayyaz; Algadi, Hassan
Abstract: The structural, elastic, charge conduction and photoresponsive properties of halide perovskites, i.e., CsBX3 (B = Pb, Sn; X = I, Br, Cl) are investigated using the full potential‐linearized augmented plane wave (FP‐LAPW) method in the frame work of density functional theory (DFT). Perdew Burke Ernzerhof (PBE) functional belonging to the generalized‐gradient approximation (GGA) is implemented. For the better estimation of electronic parameters, the Tran–Blaha modified Becke–Johnson (TB‐mBJ) potential is employed. The elastic parameters such as bulk modulus, shear modulus, Young's modulus, the Pugh's ratio, anisotropy factor, Poisson's coefficient, and melting temperature ( T m ) are estimated within Voigt‐Ruess‐Hill approximations. The energy band structure results, total density of states (TDOS), partial density of states (PDOS) outcomes, and isosurface charge density contour plots disclose that Sn 2+ and I 1− are more appropriate divalent cation and anion respectively, among all studied composites especially for the application of photoresponsive resistive random access memory (RRAM) devices. Moreover, partial density of states (PDOS) outcomes depict that conduction band formation is consequence of hybridization of electrons from p ‐orbitals of divalent cations, i.e., Pb, Sn and I/Br/Cl halogen anions. Besides, regarding charge conduction Sn‐based composites offer minimal energy bandgap as compared to Pb‐based composites. The energy bandgap order for Sn‐based compounds is found as CsSnI3 > CsSnBr3 > CsSnCl3. The optical analysis renders that CsSnI3 have the capability to absorb a wide range of ultraviolet (UV), visible and infrared (IR) electromagnetic incident radiations thus, make it much suitable material for optoelectronic memristors and associated applications. Abstract : The structural, elastic, charge conduction, and photoresponsive properties of CsBX3 (B = Pb, Sn; X = I, Br, Cl) are investigated using density functional theory (DFT). The electronic parameters disclose that Sn 2+ and I 1− are more appropriate divalent cation and anion respectively, among all studied composites especially for the application of photoresponsive resistive random access memory (RRAM) devices.